Majority World Perspectives on Christian Mission - Botha, Nico A.; Baron, Eugene (UJ Press, 2022)
It affords us real pleasure to present this editorial on behalf of the Majority World Christian Leaders Conversation (MWCLC). The MWCLC started slowly, but surely since 2016, following a groundbreaking conversation among eleven mission practitioners from the Majority World who met in the United Kingdom somewhere between London and Oxford. At the meeting, several themes emerged under the banner of missionary questions and impulses of the Majority World, from the perspective of the reign of God. These themes and more find reflection in the book. However, before proceeding to the content of the anthology, a note on the concept "Majority World" seems necessary. The time where terms like "Third World" gained strong currency, is long since gone. The term "Majority World" is a new kid on the block and requires some clarification. The use of the term is a strategy of avoiding concepts like "Developing" or "Third World" or even "Global South" which are pejorative in a real sense. To speak of the Majority World is geographically accurate in that Africa, Asia and Latin America are included.